Comprehensive guide to acetyl-carboxylases in algae. (March 2013) - Huerlimann, Roger; Heimann, Kirsten
<x xml:space="preserve">Abstract</x> Lipids from microalgae have become an important commodity in the last 20 years, biodiesel and supplementing human diets with ω-3 fatty acids are just two of the many applications. Acetyl-CoA carboxylase (ACCase) is a key enzyme in the lipid synthesis pathway. In general, ACCases consist of four functional domains: the biotin carboxylase (BC), the biotin carboxyl binding protein (BCCP), and α-and ß-carboxyltransferases (α-and ß-CT). In algae, like in plants, lipid synthesis is another function of the chloroplast. Despite being well researched in plants and animals, there is a distinct lack of information about this enzyme in the taxonomically diverse algae. In plastid-containing organisms, ACCases are present in the cytosol and the plastid (chloroplasts) and two different forms exist, the heteromeric (prokaryotic) and homomeric (eukaryotic) form. Despite recognition of the existence of the two ACCase forms, generalized published statements still list the heteromeric form as the one present in algal plastids. In this study, the authors show this is not the case for all algae. The presence of heteromeric or homomeric ACCase is dependent on the origin of plastid. The authors used ACCase amino acid sequence comparisons to show that green (Chlorophyta) and red (Rhodophyta) algae, with the exception of the green algal class Prasinophyceae, contain heteromeric ACCase in their plastids, which are of primary symbiotic origin and surrounded by two envelope membranes. In contrast, algal plastids surrounded by three to four membranes were derived through secondary endosymbiosis (Heterokontophyta and Haptophyta), as well as apicoplast containing Apicomplexa, contain homomeric ACCase in their plastids. Distinctive differences in the substrate binding regions of heteromeric and homomeric α-CT and β-CT were discovered, which can be used to distinguish between the two ACCase types. Furthermore, the acetyl-CoA binding region of homomeric α-CT can be used to distinguish between cytosolic and plastidial ACCase. The information provided here will be of fundamental importance in ACCase expression and activity research to unravel impacts of environmental and physicochemical parameters on lipid content and productivity.